Pengaruh Penerapan Strategi Solusi Bisnis Financial Ecosystem Untuk Nasabah Segmen Institusi Terhadap Pendapatan Bisnis (Studi Kasus PT Bank Negara Indonesia) - Hastari, Hastari; Syarief, Rizal; Gustari, Irvandi (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2023)
The business strategy develops according to the company's current developments. One of the strategies used in the banking business to be competitive is the differentiation strategy. Various developments in the current situation have led to changes in the need for banking. BNI continues to carry out different and innovative strategies to meet the needs of its customers. BNI through the Institutional Banking Division always implements a financial ecosystem business solution strategy for institutional segment customers. This business strategy can also increase banking business revenue. The financial ecosystem business solution strategy requires a more in-depth study to measure the effect of this strategy in generating optimal business income. This research was conducted using statistical analysis, namely the PLS Structural Equation Model (SEM). The results of the study show that the strategic solutions for the business financial ecosystem carried out have a significant positive effect on business income. This will directly or indirectly affect BNI's business revenue.